1995
DOI: 10.1016/0014-5793(95)00247-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TGF‐β1 (transforming growth factor‐β1) on the cell cycle regulation of human breast adenocarcinoma (MCF‐7) cells

Abstract: The antiproliferative effects of TGF-/31 were investigated in a human breast adenocarcinoma cell line (MCF-7). We report that TGF-I~I inhibits proliferation through cell cycle arrest in G~. A MCF-7 cell subline (MCF-7(-)), in which the type II TGF-I~ receptor is not detected, was shown to be resistant to TGF-J~I growth inhibitory effect. Cdk2 kinase activity was inhibited in the MCF-7 sensitive cell subline in parallel with the inhibition of cell cycle progression. In both sensitive and resistant cell lines, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…In the present study, it was demonstrated that recombinant TGF-β inhibited the proliferation of MCF-7 cells. This result was consistent with a previous study by Mazars et al (22). Porcine TGF-β1 was used in the study by Mazars et al (22), whereas the present study used recombinant human TGF-β, which was more suitable for the physiological conditions.…”
Section: Ink4bsupporting
confidence: 93%
“…In the present study, it was demonstrated that recombinant TGF-β inhibited the proliferation of MCF-7 cells. This result was consistent with a previous study by Mazars et al (22). Porcine TGF-β1 was used in the study by Mazars et al (22), whereas the present study used recombinant human TGF-β, which was more suitable for the physiological conditions.…”
Section: Ink4bsupporting
confidence: 93%
“…For example, lycopene like tamoxifen, pure antiestrogens, retinoids, progestins, TGF-b and TNF-a reduces cyclin D protein abundance (Jeoung et al, 1995;Mazars et al, 1995;Planas Silva and Weinberg, 1997;Watts et al, 1995). Whereas most of these agents have been shown to increase levels of the CDK inhibitors, p21 and p27, lycopene, like retinoic acid, reduces p21 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, many anticancer agents, including those used for breast cancer therapy, convey their inhibitory e ect in G 1 phase primarily by reducing cyclin D1 levels. These include pure antiestrogens (Watts et al, 1994), tamoxifen (Planas Silva and Weinberg, 1997), retinoids (Teixeira and Pratt, 1997;Zhou et al, 1997), progestins (Musgrove et al, 1998), as well as 1.25-dihydroxyvitamin D 3 (Wang et al, 1996) and TGF-b (Mazars et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor b (TGFb), a potent growth inhibitor for breast cancer cells, has been shown to directly enhance p21 expression via a TGFb responsive element in the p21 promoter (Datto et al, 1995). TGFb upregulated p21 in ovarian adenocarcinoma cells (Elbendary et al, 1994) and increased p21 nuclear localization in TGFb responsive human breast cancer MCF-7 cells in a TGFb type II receptor (RII) dependent manner (Mazars et al, 1995). TGFb receptors were found to be repressed in many malignancies including estrogen receptor positive breast cancer cell lines (Brattain et al, 1996;Kalkhoven et al, 1995) and reconstitution of a functional receptor system led to reduced malignancy (Sun et al, 1994).…”
Section: Discussionmentioning
confidence: 99%